Sorption-luminescence method for determination of ytterbium - Olha Stashkiv; Volodymyr Vasylechko; Roman Gamernyk; Yaroslav Kalychak (Taylor & Francis, 2023)
Sorption-luminescence method for ytterbium determination based on natural Transcarpathian clinoptilolite was proposed. The optimal luminophore preparation conditions are Yb(III) sorption on the precalcined at 300 °C clinoptilolite and further treatment of clinoptilolite-Yb(III) samples with 1-(2-pyridylazo)-2-naphthol and ethonium solution at pH 8.5. A sample of luminophore clinoptilolite-Yb(III)-PAN-ethonium was heated at 50°С. The linear calibration range of Yb(III) concentration with the detection limit of 5 ng·mL−1 is within 12.5–1000 ng·mL−1. The proposed method can be used for ytterbium determination in the presence of many rare earths. The method gives recoveries from 92.5% to 103% and RSD from 3.1% to 5.8% determination of ytterbium.
Сорбціонно-люмінесцентний метод визначення ітербію
Keywords: Clinoptilolite; PAN; Sorption-luminescence; determination; ytterbium